The Effect Of Financial Management Of Village Fund Allocation On The Development Of Tabbinjai Village, Gowa Regency - Muh. Alamsyah Perdana Putra; Linda Razak; Waode Rayyani (International Journal of Economic Research and Financial Accounting, 2023)
This study aims to determine the influence of village officials and village community participation on the development of the village of Tabbinjai, Gowa Regency. This type of research used in research is research with a quantitative approach using a questionnaire. The research subjects were village officials in the village of Tabbinjai, Gowa Regency and the people of Tabbinjai village. The data used is primary data in the form of questionnaire results from respondents. Respondents from the study were 120 respondents. The analysis technique used is descriptive statistics and multiple linear regression analysis. The results of the study show that village officials and village community participation have a positive and significant effect on village development. Village officials are influential because of the ability that village officials have in managing village funds. Village community participation is influential because the higher the participation, the more development of the village.